Individualised therapeutic approach to the patient with atypical haemolytic-uraemic syndrome - Ivana Mikačić; Nikolina Marić (Clinical Medicine)
Atypical haemolytic-uraemic syndrome (aHUS) is a rare disease associated with uncontrolled activation of the alternative complement pathway, leading to thrombotic microangiopathy (TMA). Early diagnosis and treatment with eculizumab, a monoclonal antibody targeting the complement component C5, are crucial to improve outcomes and prevent renal failure and mortality. Current recommendations include lifelong eculizumab therapy, yet this practice presents challenges including high treatment costs and increased infection risks from prolonged complement inhibition. We hypothesise that a personalised eculizumab dosing strategy tailored to individual patient responses could optimise therapy, reduce costs and improve safety. This hypothesis was evaluated through a presentation of a patient who was managed with a specific eculizumab treatment approach. The patient’s condition improved significantly, allowing for a gradual reduction in eculizumab dosage based on clinical response and drug level monitoring.Throughout treatment, the patient’s complement activity and eculizumab levels were closely monitored, showing that lower doses maintained therapeutic efficacy without evident TMA recurrence. This case supports the feasibility of transitioning from fixed regimens to personalised dosing strategies in managing aHUS. Such approaches could mitigate the risks and costs associated with lifelong therapy while maintaining disease control, especially considering the variability in relapse risk among different genetic mutations. This personalised treatment model might significantly impact the management of aHUS, aligning clinical care with individual patient needs and economic considerations. Further research should relate drug pharmacokinetics/pharmacodynamics to clinical/genetic setting to identify milestones of individual patient treatment approach.